Polyketides from the marine sponge Plakortis angulospiculatus - Epifanio,Rosângela de A. (2005)
Organic extracts of the marine sponge Plakortis angulospiculatus were studied from two different collections from Pernambuco State, Brazil. Bioautography with opportunistic marine pathogens, with results from the brine shrimp lethality assay, were used to guide the purification of the known furanylidenic methyl ester 1 and two new derivatives 2 and 3. The structures were elucidated by spectroscopic methods and by selective reduction of 3 into 2.